Multiple Domain Associations within the Arabidopsis Immune Receptor RPP1 Regulate the Activation of Programmed Cell Death. - Karl J Schreiber; Adam Bentham; Simon J Williams; Bostjan Kobe; Brian J Staskawicz (PLoS Pathogens)
Upon recognition of pathogen virulence effectors, plant nucleotide-binding leucine-rich repeat (NLR) proteins induce defense responses including localized host cell death. In an effort to understand the molecular mechanisms leading to this response, we examined the Arabidopsis thaliana NLR protein RECOGNITION OF PERONOSPORA PARASITICA1 (RPP1), which recognizes the Hyaloperonospora arabidopsidis effector ARABIDOPSIS THALIANA RECOGNIZED1 (ATR1). Expression of the N-terminus of RPP1, including the Toll/interleukin-1 receptor (TIR) domain ("N-TIR"), elicited an effector-independent cell death response, and we used allelic variation in TIR domain sequences to define the key residues that contribute to this phenotype. Further biochemical characterization indicated that cell death induction was correlated with N-TIR domain self-association. In addition, we demonstrated that the nucleotide-binding (NB)-ARC1 region of RPP1 self-associates and plays a critical role in cell death activation, likely by facilitating TIR:TIR interactions. Structural homology modeling of the NB subdomain allowed us to identify a putative oligomerization interface that was shown to influence NB-ARC1 self-association. Significantly, full-length RPP1 exhibited effector-dependent oligomerization and, although mutations at the NB-ARC1 oligomerization interface eliminated cell death induction, RPP1 self-association was unaffected, suggesting that additional regions contribute to oligomerization. Indeed, the leucine-rich repeat domain of RPP1 also self-associates, indicating that multiple interaction interfaces exist within activated RPP1 oligomers. Finally, we observed numerous intramolecular interactions that likely function to negatively regulate RPP1, and present a model describing the transition to an active NLR protein.